Media barometer 1996 - Nordicom - Nordic Information Centre for Media and Communication Research, University of Gothenburg (University of Gothenburg, 1998)
The first Media Barometer was conducted in 1979 and since then the survey has been carried out annually. The purpose is to explore how the Swedish population is using different media during an average day. In 1996 the respondents were asked about their usage of different media equipment such as television, text-television, radio, video recorder, CD-player/record player, and tape recorder, the day before the interview. Respondents using any of these equipments were asked about time spent using the equipment. For equipment not used the day before the respondents were asked when it was last used. Television watchers and radio listeners were asked about which channels they had watched/listened to. Video watchers were asked if they watched a recorded program, a rented movie or a movie they had bought. All respondents were asked if the had been reading any of the following the day before: morning paper, evening paper, weekly magazine, comics or any other magazine, or book. If so, they were asked how many and for how long period. Book readers were also asked what kind of literature they were reading and paper and magazine readers were asked about what kind of paper/magazine they read. Those respondents who answered that they did not read any paper, magazine or book the day before were asked when they last did so. The survey also includes detailed information on at what time the day before the respondent spent time reading morning paper, evening paper, listening to the radio or watching television. There is also more detailed information on text-television usage. The respondents also had to state what kind of advertisments they had been reading/looking to during the last week. A number of questions dealt with computer usage at home, and the usage of Internet. Background variables includes information on age, gender, education, occupation, and household composition.

Mediebarometern genomfördes första gången 1979 och har sedan dess genomförts varje år. Undersökningen avser att belysa hur stor andel av den svenska befolkningen som en genomsnittlig dag tagit del av ett antal enskilda medier. Syftet är att beskriva tendenser och förändringar i människors utnyttjande av massmedier.
Mediebarometern 1996
Keywords: newspaper readership; tidnings läsekrets; periodicals readership; tidskrifts läsekrets; listening to music; musiklyssnande; book use; bokanvändning; local broadcasting; lokalsändningar; radio stations; radiostationer; satellite television; satellit-tv; television channels; tv-kanaler; households; hushåll; radio listening; radiolyssnande; reading (activity); läsande; Media; Media; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap